Spectroscopic Proof of the Correlation between Redox‐State and Charge‐Carrier Transport at the Interface of Resistively Switching Ti/PCMO Devices. (6th April 2014) - Herpers, Anja; Lenser, Christian; Park, Chanwoo; Offi, Francesco; Borgatti, Francesco; Panaccione, Giancarlo; Menzel, Stephan; Waser, Rainer; Dittmann, Regina
<x xml:space="preserve">Abstract</x> By using hard X‐ray photoelectron spectroscopy experimentally, proof is provided that resistive switching in Ti/Pr0.48Ca0.52MnO3 (PCMO) devices is based on a redox‐process that mainly occurs on the Ti‐side. The different resistance states are determined by the amount of fully oxidized Ti‐ions in the stack, implying a reversible redox‐reaction at the interface, which governs the formation and shortening of an insulating tunnel barrier. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>